Construction of a Solar Distiller as an Alternative for the Development of Practical Classes in Teaching Chemistry (Research, Society and Development, 2019)
The discipline of chemistry is still considered difficult to understand by the students of Basic Education and this is due to the fact that they believe that this science is incomprehensible, abstract and out of their daily life and so unusable. However, this discipline is shown as a necessary science for the formation of students. Since this science studies the matter, its transformations and phenomena of nature, and is present in everyday life, it also has an indispensable role in scientific and technological development and in today's society. The objective of This work was to construct a solar distiller as an alternative to develop practical classes in the chemistry laboratory; Evaluate the efficiency of the solar distiller and the quality of distilled water and propose generating themes for various scientific subjects in high school classes. The methodology consisted of constructing the distiller, evaluating its operation for 7 days, with daily sampling of distilled water samples. From these samples, the pH, conductivity and presence of the ions chloride, carbonate, calcium and iron (II) and (III) were tested to analyze the quality of the water from the distiller, and the water supply (tap water) for comparison purposes. The Solar Distiller built with alternative materials of low cost, presented an average yield 58.7% of distilled water per day, being its viable use for laboratories of small schools that do not have a standard equipment of laboratories that Need to use distilled water to prepare solutions and other activities for practical classes. The qualitative chemical tests for the presence of ions (chlorides, carbonates and calcium) of this work were negative, but more tests would be needed to be able to certify their use for quantitative research in the scope of the research. Physicochemical Tests such as pH and conductivity were significantly better than tap water and residual condensation water from air conditioners, there is still certainty of purity suitable for use in research works. The Distiller proved very favorable for its use in practical classes of chemistry, being possible to address several subjects of the textbook.